2005
DOI: 10.1089/tmj.2005.11.137
|View full text |Cite
|
Sign up to set email alerts
|

The Essence of Telehealth Readiness in Rural Communities: An Organizational Perspective

Abstract: This paper examines telehealth readiness from an organizational perspective and explores the essence of telehealth readiness among four domains, namely, patients, practitioners, the public, and organizations in rural Canadian communities. Because readiness is a necessary requirement for the successful implementation of an innovation, it is important to identify and ensure core factors of readiness before costly investments are made. The findings presented here derive from a qualitative phenomenological researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 8 publications
0
59
0
3
Order By: Relevance
“…Another group was selected by its clinical importance: ''period of time working in primary care,'' ''usefulness of the system,'' ''connection to Internet,'' and ''negative interference in the professional role toward patients.'' 14,16,[19][20][21]23,24,26 The criterion adopted to stop the decision tree was a p value of < 0.05 (chi-squared analysis), and the predictive accuracy was evaluated by 23 Do you believe that asking for a second opinion through the teleconsultation system could negatively interfere in your professional role towards patients? 24 Do you believe that asking for a second opinion through the teleconsultation system could negatively interfere in your professional role towards the community?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another group was selected by its clinical importance: ''period of time working in primary care,'' ''usefulness of the system,'' ''connection to Internet,'' and ''negative interference in the professional role toward patients.'' 14,16,[19][20][21]23,24,26 The criterion adopted to stop the decision tree was a p value of < 0.05 (chi-squared analysis), and the predictive accuracy was evaluated by 23 Do you believe that asking for a second opinion through the teleconsultation system could negatively interfere in your professional role towards patients? 24 Do you believe that asking for a second opinion through the teleconsultation system could negatively interfere in your professional role towards the community?…”
Section: Discussionmentioning
confidence: 99%
“…Factors related to use of the teleconsultation system: Although these factors can be related to the telehealth center, to the operational system, or to the remote sites, in this study the questionnaire was applied only to professionals in remote sites, even though it included questions about their evaluation of factors related to the center and system. The questionnaire consisted of 27 questions about factors grouped into seven categories: institutional, 14 organizational, [15][16][17] infrastructure, 6,14,18 technical, 6,19,20 socioeconomic, [19][20][21][22] human, 17,23,24 and educational. 25 Answers were given in a 4-or 5-point scale.…”
Section: The Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…The poor contextualization has been the cause for the lack of an appropriate framework or model to be used for e-health readiness assessment in developing countries. Several studies such as (Jennett et al, 2005;Khoja, 2007;Ojo et al, 2008;Li & Seale, 2012;Rezai-Rad, 2012) recommended the importance of considering the context, while developing a model for e-health assessment in developing countries. From the reviewed literature, brain storming sessions and workshops, this study identified five categories of factors that are needed to assess e-health readiness in developing countries.…”
Section: The Electronic Journal Of Information Systems In Developing mentioning
confidence: 99%